Microplastic enrichment and detection method for surface water body
By using the carbon quantum active site powder powder adsorbent in the water body, it is rich in micro -plastic in the water body, and combined with the liquid color spectrum spectrum combined instrument for detection, solving the complexity and efficiency of micro -plastic enrichment and detection in existing technologies. Achieve efficient and accurate micro -plastic removal and detection.
Patent Information
- Application Number
- CN202411831108.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The prior art has problems such as complex operation, low separation efficiency and large detection data in the enrichment and detection of microplastics in water bodies.
The carbon quantum dot active site powder is used as the adsorbent, and a reaction is formed by reacting with the micro -plastic in the surface of the surface, and the micro -plastic is used for quantitative detection of micro -plastic with liquid chromatography spectrum.
It achieves rapid, efficient enrichment and accurate detection of microplastics in water bodies, reducing the impact on the environment and damage to other organisms.
Smart Images

Figure CN119335100A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental protection and pollutant treatment, and specifically relates to the field of microplastic treatment, and in particular to a method for enriching and detecting microplastics in surface water. Background Art
[0002] Plastics are widely used in daily life, but due to their high recycling costs, the recycling rate is not high. And its difficulty in degradation makes it exist in the environment for a long time. Plastics in the environment are further decomposed into smaller plastic fragments or particles through physical and chemical effects. When their diameter is less than 5mm, they can be defined as microplastics. Such plastic particles will not be degraded by the natural environment, but will remain in the environment and even enter the body, bringing environmental health risks. Therefore, there is an urgent need for a method to enrich microplastics in water bodies and remove the enriched microplastics. At the same time, an accurate, sensitive, convenient and fast method is also needed to quantitatively detect microplastics in water bodies. Transferring pollutants from liquid phase to solid phase through adsorption treatment has the characteristics of high efficiency and easy operation. However, for the separation and quantification of microplastics, the density separation method is currently widely used, such as immersion separation of sediment samples using saturated sodium chloride solution, sodium polytungstate solution or seawater. However, the material composition in actual environmental samples is relatively complex, the operation of the above method is complicated, and the separation efficiency still needs to be further improved.
[0003] The Chinese patent with publication number CN105651748B discloses a method for quantitative detection of microplastics in aquatic organisms based on fluorescent tracing technology. By selecting fluorescently labeled microplastic particles as the test object, digesting the tissue with nitric acid, and fixing the obtained digestion solution; preparing fluorescent microplastic suspension solutions with different concentration gradients, and obtaining a standard curve based on the fluorescence value measured by a fluorescence spectrometer; measuring the fluorescence value of the sample solution, and obtaining the microplastic content in the corresponding tissue sample based on the standard curve. The technical solution of this invention can effectively and accurately quantify microplastics ingested into aquatic organisms, but this method has great limitations and is complicated to operate.
[0004] The Chinese patent with the publication number CN107966393B discloses a method for determining the content of microplastics in seawater and the absorption of microplastics by organisms, which collects seawater from the environment into a container; places a viscous fluorescent material in the container and stirs it to fluorescently mark the microplastics in the seawater; adds a certain amount of seawater density solution and stirs it; removes the static sediment at the bottom of the container and uses a fluorescence spectrometer to measure the concentration of fluorescent microplastics in the seawater; places living marine organisms in the container and cultivates them for a period of time; after removing the living marine organisms, uses a fluorescence spectrometer to measure the concentration of fluorescent microplastics in the seawater in the container; dissects the living marine organisms, collects target tissues and organs, and measures the concentration of fluorescent microplastics in each target tissue and organ. Because this method does not have a directional mark for microplastics, other solid particles in the seawater will also be marked by the fluorescent powder, making the obtained detection data larger.
[0005] Since a large amount of plastic waste is discharged into rivers and discarded into the ocean, the amount of microplastics in the water environment is far beyond our imagination. Microplastics are also mobile and can flow with water or be ingested by aquatic plants and animals, posing a serious threat to the ecological environment and human health. Simply applying plastic-degrading bacteria will increase the content of microplastics in water bodies and aggravate microplastic pollution, especially microplastics smaller than 10 μm, because the particles are small and light and difficult to capture and enrich. Therefore, the effective enrichment of microplastics in water bodies is a hot topic in the current research field of microplastic removal in water bodies, and it is of great significance to actively explore a method for enriching and detecting microplastics in water bodies. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide a method for enriching and detecting microplastics in surface water, so as to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.
[0007] In view of this, one of the main purposes of the present invention is to propose a method for enriching and separating microplastics in an aquatic environment, in order to at least partially solve at least one of the above-mentioned technical problems.
[0008] In order to solve the problem of enrichment of microplastics and solve the technical problems of low adsorption capacity and slow adsorption rate of enrichment materials, the present invention aims to develop enrichment materials with excellent adsorption performance and provide a method for enriching microplastics in surface water, specifically: First, adsorbents are added to water samples of surface water bodies containing microplastics for adsorption and enrichment to form aggregates; then, the microplastics are filtered to complete the enrichment; digestion solution is used to dissolve and elute the microplastics on the aggregates, and finally, the concentration of microplastics in the environmental water samples is determined by liquid chromatography-mass spectrometry.
[0009] The microplastics include but are not limited to at least one of polystyrene, polyethylene, polypropylene, polyvinyl chloride, polyethylene terephthalate, and polymethyl methacrylate.
[0010] The adsorbent is a carbon quantum dot active site powder, and the preparation steps are as follows: S001, stirring and heating chitosan and deionized water at 100°C for 80 to 120 minutes until they are completely dissolved to obtain a chitosan aqueous solution; The mass concentration of the chitosan aqueous solution is 10-15%; S002, dissolve sodium hydroxide and deionized water and add them uniformly, add lignin, and stir for 30 to 50 minutes until the lignin is completely dissolved; add chitosan aqueous solution, then add polyethyleneimine, stir uniformly, and react at 50 to 60° C. for 2 to 3 hours to allow lignin, chitosan and polyethyleneimine to undergo cross-linking reaction to obtain a solution containing lignin grafted with amine groups; the mass concentration of the sodium hydroxide aqueous solution is 25%; The mass ratio of polyethyleneimine, chitosan and lignin is 3-4:5-8:50-60; S003, dissolving monochloroacetic acid in deionized water, adding the monochloroacetic acid solution dropwise to the lignin solution finally obtained in S002, heating to 80-90°C for reaction for 4-5 hours, cooling after the reaction, pouring out the reaction solution, adjusting the solution pH to 5.0±0.1 with 2 mol / L hydrochloric acid, filtering the reaction product with a 0.5 μm microporous membrane to remove impurities, and then dialyzing it in deionized water with a 1000 da dialysis bag for 24 hours, and freeze-drying it for 72 hours to obtain a carbon quantum dot active site powder, wherein the mass concentration of the monochloroacetic acid solution is 60%, and the mass ratio of monochloroacetic acid to lignin is 6:50-60.
[0011] Through a two-step reaction, lignin was grafted with amine and carboxyl groups, and chlorine was introduced to obtain a carbon quantum dot active site powder with a positive charge on the surface. The powder has the ability to selectively adsorb microplastics, especially for microplastics with particularly small particles in water. It has a very good flocculation ability. Since the surface of suspended microplastic particles in the water body is negatively charged, when there is no carbon quantum dot active site powder adsorbent in the water, the microplastics remain stable due to mutual electrostatic repulsion. After adding the carbon quantum dot active site powder adsorbent, the surface charge of the microplastics will be neutralized, and when the surface charge of the dispersed microplastics is completely neutralized by a certain amount of carbon quantum dot active site powder adsorbent, the electrostatic repulsion is reduced to a minimum. At this time, the microplastics can gather together and form large-particle floccules. However, when an excessive amount of carbon quantum dot active site powder adsorbent is added, the microplastic particles will adsorb too much positive charge, the potential of the microplastics will reverse, and become positively charged microplastics, re-forming a stable state, and when the surface charge of the microplastics changes from negative to positive, the microplastic removal efficiency decreases while the charge is reversed. This indicates that the microplastics in the system have re-stabilized, especially those with a particle size of less than 10 μm, which are particularly prone to re-stabilization and cannot be efficiently enriched. Therefore, single charge neutralization is not effective for enriching microplastics of all particle sizes, especially small particles.
[0012] Therefore, further, the carbon quantum dot active site powder and montmorillonite are compounded to obtain a carbon quantum dot active site microporous adsorbent, specifically: S101, selecting calcium-based montmorillonite, adding the calcium-based montmorillonite to deionized water, adding dilute hydrochloric acid and stirring evenly, so that the calcium-based montmorillonite is dispersed in the dilute hydrochloric acid solution, heating to 60° C., adding dimethyldiallyl ammonium chloride, stirring fully, reacting for 1 to 2 hours, and obtaining an aminated montmorillonite suspension, adjusting the pH value to 5.0 to 5.5, adding histidine, stirring fully, and reacting for 1 to 2 hours to obtain an aminated montmorillonite microsphere suspension with a negative charge on the outside and a high density of cations on the inside; wherein the mass ratio of dimethyldiallyl ammonium chloride to calcium-based montmorillonite is 1:20; the mass ratio of the histidine to calcium-based montmorillonite is 1:4 to 5; S102, dissolving the carbon quantum dot active site powder in a citric acid aqueous solution with a mass concentration of 8% to activate the active sites on the carbon quantum dot active site powder, and then adding the suspension of aminated montmorillonite microspheres with a negative charge on the outside and a high density of cations on the inside obtained in S101, reacting at 50-60°C for 2-3 hours to allow the carbon quantum dot active site powder and montmorillonite microspheres to fully react and cross-link, filtering, and low-temperature drying to obtain a carbon quantum dot active site microporous adsorbent.
[0013] The surface layer of the adsorbent has positively charged carbon quantum dot active sites coated with an intermediate layer of negatively charged aminated montmorillonite, which has a high density of cationic groups inside. When there are microplastics in the water body, when the microplastics are in charge balance, the carbon quantum dot active site microporous adsorbent can adjust its own charge, break this balance, make the adsorption speed faster, and the enrichment effect better. This is because montmorillonite has a large number of pores and surface active sites, which can effectively adsorb and exchange cations to obtain better adsorption groups. In addition, montmorillonite can also enhance its adsorption capacity by changing its chemical properties and surface morphology. By introducing carbon quantum dot active sites with cations, a carbon quantum dot active site microporous adsorbent is further obtained, making it more capable of adsorbing negatively charged microplastics. Lignin carbon quantum dots are used to compound with montmorillonite to increase the specific surface area of montmorillonite and change the charge structure of the montmorillonite surface, so that the negative charge on the surface of montmorillonite and the positive charge in the inner layer can be converted to each other, thereby improving its adsorption capacity, accelerating the adsorption speed of microplastics in water, improving the adsorption capacity of microplastics in water, and realizing the rapid enrichment and separation of microplastics in water. Carbon quantum dot active site microporous adsorbents are highly selective and can selectively adsorb microplastic particles without affecting other substances in the environment, which can reduce the impact on the environment and damage to other organisms.
[0014] At the same time, the use of carbon quantum dot active site microporous adsorbents for microplastic enrichment and separation has better environmental friendliness and biocompatibility. Therefore, carbon quantum dot active site microporous adsorbents have high efficiency, high selectivity, good reproducibility, and high safety.
[0015] Furthermore, a method for detecting microplastics in surface water is provided, specifically: S201, adding sodium carbonate to a water sample of a surface water body containing microplastics to adjust the pH value to 8.0-8.5, and then adding an adsorbent to perform adsorption treatment, so that the adsorbent is in full contact with the microplastics, adsorbing the negatively charged microplastics, and forming multiple aggregate centers; The adsorption treatment time is 40 to 50 minutes; the mass ratio of the adsorbent to the water sample of the surface water body containing microplastics is 0.1 to 2:100.
[0016] In a weakly alkaline environment, the carbon quantum dot active site microporous adsorbent releases negative charges, which changes the charge balance of the carbon quantum dot active site microporous adsorbent, causing the negative charge on the montmorillonite surface and the released negative charge to repel each other, activating the high-density cationic groups inside, releasing cations, adsorbing negatively charged microplastics, and forming aggregates. Due to the excess of carbon quantum dot active site microporous adsorbent, when the aggregates become positively charged due to the saturated surface of adsorption, the negative charge released by the carbon quantum dot active site microporous adsorbent in the water body and the negative charge on the surface of the carbon quantum dot active site microporous adsorbent itself become another adsorption center, which continues to adsorb the aggregates, and the aggregates continue to grow and then precipitate.
[0017] S202, filtering the surface water sample containing the aggregates with a microporous membrane to obtain the aggregates, thereby completing the enrichment and separation of the microplastics; The microporous membrane is a glass fiber membrane, and the pore size of the microporous membrane is 0.5 to 1 μm; S203, dissolve the microplastics on the eluted aggregates with digestion solution and collect the washed liquid, concentrate it to 1 mL, blow dry it with a nitrogen blower, add chromatographic grade methanol, transfer it to a brown injection bottle, and make up to 2 mL; use liquid chromatography-mass spectrometry to determine the content of microplastics.
[0018] The digestion solution is a mixture obtained by mixing tetrahydrofuran and dichloromethane in a mass ratio of 1:3; This method based on liquid chromatography-mass spectrometry for quantitative detection of microplastics in water bodies is used in monitoring microplastic surface water environmental pollution.
[0019] The adsorption of carbon quantum dot active site microporous adsorbent includes three stages: rapid adsorption in the early stage, slow adsorption in the middle stage, and balanced adsorption in the late stage. The first 10 minutes is the rapid adsorption period. Due to the effect of charge, the carbon quantum dot active site microporous adsorbent has a strong adsorption capacity for microplastics and a fast adsorption speed. The adsorption type is mainly surface adsorption and diffusion. At the same time, the positively charged carbon quantum dots play a bridging role in the adsorption process. In the middle stage of 10 to 20 minutes, the slow adsorption occurs. At this time, microplastics diffuse internally in the lamellar structure of the carbon quantum dot active site microporous adsorbent, diffusing from the surface to the depth of the pores. The charge in the lamellar structure is released, breaking the charge balance of the system again, making the later adsorption appear in the third stage of balanced adsorption with strong adsorption capacity and fast adsorption speed, so that the microplastics in the water are quickly enriched.
[0020] Carbon quantum dot active site microporous adsorbents can interact with microplastics through charge adsorption and hydrogen bonding. The hydroxyl, carboxyl, and amine groups on the surface of the carbon quantum dot active site microporous adsorbent increase the active sites for interaction between microplastics and adsorbents. When one end of the carbon quantum dot adsorbs a microplastic particle and the other end adsorbs another microplastic particle, a "microplastic-carbon quantum dot-microplastic" floccules can be formed. At the same time, the positively charged carbon quantum dots play a bridging role in the adsorption process. The floccules are continuously bridged to form aggregates, which then settle down, completing rapid enrichment and separation, and achieving the enrichment of microplastics in surface waters.
[0021] Compared with the prior art, the beneficial effects of the invention are: 1) The present invention provides a method for enriching and separating microplastics in surface water. Through a two-step reaction, lignin is grafted with amino groups and carboxyl groups, and chlorine is introduced to obtain a carbon quantum dot active site powder with a positive charge on the surface. The powder has the ability to selectively flocculate microplastics, especially microplastics with particularly small particles in water bodies. It has very good flocculation ability. In order to overcome the re-stabilization phenomenon of microplastics, the carbon quantum dot active site powder and the modified montmorillonite are cross-linked to obtain a carbon quantum dot active site microporous adsorbent, so that the prepared carbon quantum dot active site microporous adsorbent has many surface functional groups and active sites, which can enhance the interaction with microplastics. At the same time, the negative charge on the surface of the montmorillonite and the positive charge on the inner layer can be converted to each other, thereby improving its adsorption capacity, accelerating the adsorption speed of microplastics in the water body, improving the adsorption capacity of microplastics in the water body, and realizing the rapid enrichment and separation of microplastics in the water body. Carbon quantum dot active site microporous adsorbents are highly selective and can selectively adsorb microplastic particles without affecting other substances in the environment, which can reduce the impact on the environment and damage to other organisms.
[0022] 2) The present invention uses dimethyldiallylammonium chloride to increase the space of the calcium-based montmorillonite layer structure, increase the wrinkles inside the montmorillonite, increase the pore structure, increase the specific surface area, add histidine, change the charge distribution inside and outside the montmorillonite, and through the synergistic effect of the carbon quantum dot active site powder, not only the microporous structure on the surface is increased, the specific surface area is further expanded, and the adsorption active sites are increased, the adsorption content of microplastics is increased, thereby improving the removal rate; the adsorption effect on microplastics is very effective in a relatively short time. It is verified that it has certain feasibility and application prospects as an adsorption material in the treatment of microplastic pollution in water, providing new ideas for the treatment of microplastics in water.
[0023] 3) The method for determining the content of microplastics in surface water provided by the present invention can directly enrich and detect the content of microplastics in various surface water environments, provide accurate and effective data reference for microplastics in real environments, and provide a basis for environmental protection and microplastic control. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 , enrichment and separation curves of microplastics of the adsorbents prepared in Example 1, Comparative Example 1 and Comparative Example 4 as the adsorption time changes; Figure 2 , electron microscopic image of the carbon quantum dot active site microporous adsorbent prepared in Example 1; Figure 3 , electron micrograph of the carbon quantum dot active site microporous adsorbent prepared in Example 1 after adsorbing microplastics. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content described in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally. Example 1 A method for enriching and detecting microplastics in surface water. First, an adsorbent is prepared. The steps for preparing the carbon quantum dot active site powder are as follows: 10 parts of chitosan and 90 parts of deionized water were stirred and heated at 100°C for 120 min until completely dissolved to obtain a 10% chitosan aqueous solution; Dissolve 10 parts of sodium hydroxide and 40 parts of deionized water and add them uniformly, add 50 parts of lignin, stir for 30 minutes, until the lignin is completely dissolved; add 50 parts of chitosan aqueous solution, then add 4 parts of polyethyleneimine, stir uniformly, react at 60°C for 3 hours to allow lignin, chitosan and polyethyleneimine to undergo cross-linking reaction, and obtain a solution containing lignin grafted with amine groups; 6 parts of monochloroacetic acid were dissolved in 10 parts of deionized water, and the monochloroacetic acid solution was added dropwise to the lignin solution obtained, and the temperature was raised to 90°C for reaction for 5 hours. After the reaction was completed, the reaction solution was cooled, and the reaction solution was poured out. The pH value of the solution was adjusted to 5.0 with 2 mol / L hydrochloric acid. The reaction product was filtered with a 0.5 μm microporous membrane to remove impurities, and then dialyzed in deionized water with a 1000 da dialysis bag for 24 hours, and freeze-dried for 72 hours to obtain a carbon quantum dot active site powder; Further, a carbon quantum dot active site microporous adsorbent is prepared, specifically: 50 parts of calcium montmorillonite were selected, and the calcium montmorillonite was added to 50 parts of deionized water, and 10 parts of 5% citric acid aqueous solution were added and stirred evenly to disperse the calcium montmorillonite in the dilute hydrochloric acid solution, and the temperature was raised to 60°C, and 2.5 parts of dimethyldiallyl ammonium chloride were added, and the mixture was stirred fully and reacted for 2 hours to obtain an aminated montmorillonite suspension, and the pH value was adjusted to 5.2, and 10 parts of histidine were added, and the mixture was stirred fully and reacted for 2 hours to obtain an aminated montmorillonite microsphere suspension with a negative charge on the outside and a high density of cations on the inside; Dissolve 10 parts of carbon quantum dot active site powder in 10 parts of 5% citric acid aqueous solution to activate the active sites on the carbon quantum dot active site powder, then add it to a suspension of aminated montmorillonite microspheres with negative charges on the outside and high-density cations on the inside, react at 60° C. for 3 hours to allow the carbon quantum dot active site powder and montmorillonite microspheres to fully react and cross-link, filter, and dry at low temperature to obtain a carbon quantum dot active site microporous adsorbent; Finally, a method for enrichment and detection of microplastics in surface water is provided, specifically: Add 0.1 parts of carbon quantum dot active site microporous adsorbent to 100 parts of surface water samples containing microplastics, then add sodium carbonate aqueous solution to adjust the pH value to 8.0, and perform adsorption treatment for 50 minutes to allow the adsorbent to fully contact the microplastics and adsorb negatively charged microplastics to form multiple aggregate centers; then use a 0.5 μm microporous membrane to filter the surface water sample containing aggregates to obtain aggregates, thereby completing the enrichment and separation of the microplastics; A digestion solution was obtained by mixing 1 part of tetrahydrofuran and 3 parts of dichloromethane. The digestion solution was used to dissolve the microplastics on the eluted aggregates, and the washed liquid was collected and concentrated to 1 mL. The liquid was blown dry with a nitrogen blower, chromatographic grade methanol was added, and the volume was transferred to a brown injection bottle and fixed to 2 mL. The content of microplastics was determined by liquid chromatography-mass spectrometry.
[0026] Example 2 A method for enriching and detecting microplastics in surface water. First, an adsorbent is prepared. The steps for preparing the carbon quantum dot active site powder are as follows: 15 parts of chitosan and 85 parts of deionized water were stirred and heated at 100°C for 100 min until completely dissolved to obtain a 15% chitosan aqueous solution; Dissolve 10 parts of sodium hydroxide and 40 parts of deionized water and add them uniformly, add 50 parts of lignin, stir for 50 minutes, until the lignin is completely dissolved; add 50 parts of chitosan aqueous solution, then add 3 parts of polyethyleneimine, stir uniformly, react at 60°C for 2 hours to allow lignin, chitosan and polyethyleneimine to undergo cross-linking reaction, and obtain a solution containing lignin grafted with amine groups; 6 parts of monochloroacetic acid were dissolved in 10 parts of deionized water, and the monochloroacetic acid solution was added dropwise to the lignin solution obtained, and the temperature was raised to 90°C for reaction for 4 hours. After the reaction was completed, the reaction solution was cooled, and the reaction solution was poured out. The pH value of the solution was adjusted to 5.1 with 2 mol / L hydrochloric acid. The reaction product was filtered with a 0.5 μm microporous membrane to remove impurities, and then dialyzed in deionized water with a 1000 da dialysis bag for 24 hours, and freeze-dried for 72 hours to obtain a carbon quantum dot active site powder; Further, a carbon quantum dot active site microporous adsorbent is prepared, specifically: 50 parts of calcium montmorillonite were selected, and the calcium montmorillonite was added to 50 parts of deionized water, and 10 parts of 5% citric acid aqueous solution were added and stirred evenly to disperse the calcium montmorillonite in the dilute hydrochloric acid solution, and the temperature was raised to 60°C, and 2.5 parts of dimethyldiallyl ammonium chloride were added, and the mixture was stirred fully and reacted for 2 hours to obtain an aminated montmorillonite suspension, and the pH value was adjusted to 5.5, and 12 parts of histidine were added, and the mixture was stirred fully and reacted for 2 hours to obtain an aminated montmorillonite microsphere suspension with a negative charge on the outside and a high density of cations on the inside; Dissolve 10 parts of carbon quantum dot active site powder in 10 parts of 5% citric acid aqueous solution to activate the active sites on the carbon quantum dot active site powder, then add it to a suspension of aminated montmorillonite microspheres with negative charges on the outside and high-density cations on the inside, react at 50°C for 3 hours to allow the carbon quantum dot active site powder and montmorillonite microspheres to fully react and cross-link, filter, and dry at low temperature to obtain a carbon quantum dot active site microporous adsorbent; Example 3 A method for enriching and detecting microplastics in surface water. First, an adsorbent is prepared. The steps for preparing the carbon quantum dot active site powder are as follows: 12 parts of chitosan and 88 parts of deionized water were stirred and heated at 100°C for 80 min until completely dissolved to obtain a 12% chitosan aqueous solution; Dissolve 10 parts of sodium hydroxide and 40 parts of deionized water and add them uniformly, add 60 parts of lignin, stir for 30 minutes, until the lignin is completely dissolved; add 50 parts of chitosan aqueous solution, then add 3 parts of polyethyleneimine, stir uniformly, react at 60°C for 3 hours to allow lignin, chitosan and polyethyleneimine to undergo cross-linking reaction, and obtain a solution containing lignin grafted with amine groups; Dissolve 6 parts of monochloroacetic acid in 10 parts of deionized water, add the monochloroacetic acid solution drop by drop into the lignin solution, heat to 90°C and react for 5 hours, cool after the reaction, pour out the reaction solution, adjust the solution pH to 4.9 with 2 mol / L hydrochloric acid, filter the reaction product with a 0.5 μm microporous membrane to remove impurities, and then dialyze in deionized water with a 1000 da dialysis bag for 24 hours, and freeze-dry for 72 hours to obtain carbon quantum dot active site powder; Further, a carbon quantum dot active site microporous adsorbent is prepared, specifically: 50 parts of calcium montmorillonite were selected, and the calcium montmorillonite was added to 50 parts of deionized water, and 10 parts of 5% citric acid aqueous solution were added and stirred evenly to disperse the calcium montmorillonite in the dilute hydrochloric acid solution, and the temperature was raised to 60°C, and 2.5 parts of dimethyldiallyl ammonium chloride were added, and the mixture was stirred fully and reacted for 2 hours to obtain an aminated montmorillonite suspension, and the pH value was adjusted to 5.3, and 10 parts of histidine were added, and the mixture was stirred fully and reacted for 2 hours to obtain an aminated montmorillonite microsphere suspension with a negative charge on the outside and a high density of cations on the inside; 12 parts of carbon quantum dot active site powder were dissolved in 10 parts of 5% citric acid aqueous solution to activate the active sites on the carbon quantum dot active site powder, and then added to a suspension of aminated montmorillonite microspheres with negative charges on the outside and high density of cations on the inside, reacted at 60°C for 3 hours to allow the carbon quantum dot active site powder and montmorillonite microspheres to fully react and cross-link, filtered, and low-temperature dried to obtain a carbon quantum dot active site microporous adsorbent; Comparative Example 1: An equal amount of carbon quantum dot active site powder was used to replace the carbon quantum dot active site microporous adsorbent for adsorption enrichment, and the rest was the same as in Example 1; Comparative Example 2: A product obtained by cross-linking carbon quantum dot active site powder and ordinary calcium-based montmorillonite was used as an adsorbent, and the other conditions were the same as those in Example 1; Comparative Example 3, there is no cross-linked carbon quantum dot active site powder, and modified calcium-based montmorillonite is directly used as an adsorbent to replace the carbon quantum dot active site microporous adsorbent in equal amounts for adsorption enrichment, and the rest is the same as Example 1; Comparative Example 4, a magnetic porous graphene adsorbent prepared in Example 1 of the method for removing microplastics in water based on graphene materials disclosed in Chinese patent publication number CN111569829B was used to replace the carbon quantum dot active site microporous adsorbent in equal amounts for adsorption enrichment, and the rest was the same as Example 1; Performance test 1. The specific surface area of the adsorbent was measured using a JW-BK200C specific surface area and pore size analyzer. The adsorbent sample was first vacuum degassed at 100°C for 8 hours, and then an N2 adsorption-desorption experiment was performed in a liquid nitrogen environment. The adsorbent samples in Examples 1-3 and Comparative Examples 1-4 were tested to obtain the specific surface area (m 2 / g) and porosity (%), as shown in Table 1. From this, it can be seen that the adsorbents involved in Examples 1-3 have larger specific surface area and porosity, and have a more significant promoting effect on the adsorption of microplastics.
[0027] Table 1 Performance characterization data of adsorbent
[0028] 2. Scanning electron microscopy The morphology of the samples was observed using a field emission scanning electron microscope Nova NanoSEM450 from FEI. Before the test, the carbon quantum dot active site microporous adsorbent sample in Example 1 was evenly dispersed on the conductive glue, and the scanning electron microscope parameters were adjusted to set the acceleration voltage, detection current 10mA, resolution 1.7nm, and magnification 500 times; the morphology is shown in Figure 2 .
[0029] A polystyrene microplastic dispersion with an average particle size of 0.1 to 1 μm and a concentration of 1.0 g / kg was prepared. The solvent was ethanol and distilled water in a volume ratio of 1:1. Ultrasonic dispersion was performed during the preparation process until uniform. 1 kg of polystyrene microplastic dispersion was taken and 1 g of the carbon quantum dot active site microporous adsorbent in Example 1 was placed. After adsorption for 50 minutes, the obtained agglomerates were filtered and dried, and then evenly dispersed on the conductive glue. The scanning electron microscope parameters were adjusted, and the acceleration voltage was set, the detection current was 10 mA, the resolution was 1.7 nm, and the magnification was 300 times; the morphology is shown in FIG. Figure 3 Depend on Figure 2 It can be seen that the carbon quantum dot active site microporous adsorbent is a spherical microporous structure with a relatively uniform size and a three-dimensional porous structure. There are many fine pore structures on the sphere. This special morphology has a high specific surface area and a large number of active sites, which can selectively and efficiently adsorb tiny microplastic particles in water. Figure 3 It can be seen that many irregular spherical particles are evenly adsorbed on the aggregates obtained after adsorption equilibrium in the water body. This shows that a large number of active sites are evenly dispersed on the spherical surface of the carbon quantum dot active site microporous adsorbent, which has a very good adsorption and enrichment effect on microplastics.
[0030] 3. Adsorption effect test of adsorbent The experiment involved making three kinds of microplastic materials, polypropylene, polystyrene and polyvinyl chloride, and crushing them into two kinds of microplastic particles with different particle sizes, with the particle size range of 0.01-10μm and 10-100μm accounting for half each. They were added into deionized water to prepare a simulated water sample containing microplastics with a microplastic concentration of 1.0mg / L and a water temperature of 27℃. 1 g of each of the adsorbents in Example 1, Comparative Example 1 and Comparative Example 4 was added to 1 kg of water sample containing microplastics for adsorption for 50 minutes, and the curve of the adsorption amount of microplastics by the adsorbent material over time was recorded. Figure 1 The horizontal axis is the adsorption time, and the vertical axis is the amount of microplastics adsorbed by the adsorption material. Figure 1It can be seen that the adsorption capacity of microplastics by the carbon quantum dot active site microporous adsorbent can basically reach a saturated adsorption capacity of 641 mg / g in about 40 minutes. Therefore, the carbon quantum dot active site microporous adsorbent has excellent adsorption capacity for microplastics of various particle sizes, especially significantly improving the capture capacity of 0.01-10 μm, achieving a very good adsorption effect. However, because of its small specific surface area and limited microporous structure, although Comparative Example 1 can adsorb microplastics, its adsorption capacity is limited and it only plays a small flocculation role. The adsorption capacity of Comparative Example 4 is about 219 mg / g. Analysis of the reason may be that its capture capacity for 0.01-10 μm is relatively poor, and 10-100 μm microplastics, because of their large particles, when their adsorption equilibrium is reached, it is easy to hinder their capture of microplastics of other particle sizes. The carbon quantum dot active site microporous adsorbent of Example 1 has convertible charge properties. When the adsorption reaches a bottleneck, the preferentially adsorbed small-particle microplastics enter the micropores due to the charge effect, changing the charge balance of the carbon quantum dot active site microporous adsorbent and disrupting the charge balance of the restabilization phenomenon. The negative charge on the surface of montmorillonite and the positive charge in the inner layer can be converted into each other, thereby improving its adsorption capacity, accelerating the adsorption rate of microplastics in water, improving the adsorption capacity of microplastics in water, and realizing rapid enrichment and separation of microplastics in water.
[0031] The test was conducted by adding homemade microplastic particles with a particle size of less than 1 μm: polypropylene microplastics, polystyrene microplastics, and polyvinyl chloride microplastics, to deionized water to simulate a water sample containing microplastics with a microplastic concentration of 0.5 mg / kg and a water temperature of 27°C. 1 g of the adsorbents of Examples 1-3 and Comparative Examples 1-4 were added to 1 kg of a water sample containing microplastics, and the removal rates were measured, as shown in Table 2. Table 2 Adsorption effect record of adsorbent
[0032] 4. Determination of microplastics in actual surface waters First, 5kg of different water samples collected from actual environmental water bodies were passed through a glass fiber membrane with a pore size of 200μm to remove the interference of large particle impurities in the water body. Then, the separation and enrichment method in Example 1 of the present invention was used for enrichment determination, mainly including: adding sodium carbonate aqueous solution to 5kg environmental water samples to adjust the pH value to 8.0, adding 5g of carbon quantum dot active site microporous adsorbent, and fully shaking for 50 minutes to allow the two to fully react. After sufficient reaction, agglomerates are formed. The obtained liquid is filtered through a glass fiber membrane, then dissolved and eluted with a digestion solution, the washing liquid is collected, and then concentrated to 1mL, blown dry with a nitrogen blower, chromatographic grade methanol is added, transferred to a brown injection bottle, and the volume is fixed to 2mL; the content of microplastics is determined by liquid chromatography-mass spectrometry. The results are shown in Table 3. By combining the separation and enrichment method with a high enrichment multiple in the present invention, the accurate mass concentration of microplastics in the water environment can be determined.
[0033] Table 3. Results of the determination of microplastics in actual surface waters
[0034] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Any equal modifications and changes made to the technical solution of the present invention by ordinary persons in the art, as long as they do not deviate from the overall concept of the present invention, are still within the scope of the present invention.
Claims
1. A method for enriching and detecting microplastics in surface water, characterized in that: First, add adsorbent to the water sample of the surface water containing microplastics for adsorption enrichment to form aggregates; then filter to complete the enrichment of microplastics; then use digestion solution to dissolve and elute the microplastics on the aggregates, and finally determine the concentration of microplastics in the environmental water sample by liquid chromatography-mass spectrometry; specifically: S201, adding a sodium carbonate aqueous solution to a water sample of a surface water body containing microplastics to adjust the pH value to 8.0-8.5, and then adding an adsorbent to perform an adsorption treatment so that the adsorbent is in full contact with the microplastics, adsorbing the negatively charged microplastics to form multiple aggregate centers; S202, filtering the surface water sample containing the aggregates with a microporous membrane to obtain the aggregates, thereby completing the enrichment and separation of the microplastics; S203, dissolve the microplastics on the eluted aggregates with a digestion solution, collect the washed liquid, concentrate it to 1 mL, blow it dry with a nitrogen blower, add chromatography-grade methanol, transfer it to a brown injection bottle, and make up to 2 mL; determine the content of microplastics using a liquid chromatography-mass spectrometer; The adsorbent is a carbon quantum dot active site microporous adsorbent, which is prepared from carbon quantum dot active site powder and modified montmorillonite.
2. The method for enriching and detecting microplastics in surface water according to claim 1, characterized in that: The carbon quantum dot active site powder is prepared by the following steps: S001, stirring and heating chitosan and deionized water at 100°C for 80-120 min until completely dissolved, to obtain a chitosan aqueous solution; The mass concentration of the chitosan aqueous solution is 10-15%; S002, dissolve sodium hydroxide and deionized water and add them uniformly, add lignin, and stir for 30 to 50 minutes until the lignin is completely dissolved; add chitosan aqueous solution, then add polyethyleneimine, stir uniformly, and react at 50 to 60° C. for 2 to 3 hours to allow lignin, chitosan and polyethyleneimine to undergo cross-linking reaction to obtain a solution containing lignin grafted with amine groups; the mass concentration of the sodium hydroxide aqueous solution is 25%; S003, dissolving monochloroacetic acid in deionized water, adding the monochloroacetic acid solution dropwise to the lignin solution finally obtained in S002, heating to 80-90°C for reaction for 4-5 hours, cooling after the reaction, pouring out the reaction solution, adjusting the solution pH to 5.0±0.1 with 2 mol / L hydrochloric acid, filtering the reaction product with a 0.5 μm microporous membrane to remove impurities, and then dialyzing it in deionized water with a 1000 da dialysis bag for 24 hours, and freeze-drying it for 72 hours to obtain a carbon quantum dot active site powder; wherein the mass concentration of the monochloroacetic acid solution is 60%, and the mass ratio of monochloroacetic acid to lignin is 6:50-60.
3. The method for enriching and detecting microplastics in surface water according to claim 2, characterized in that: The mass ratio of polyethyleneimine, chitosan and lignin is 3-4:5-8:50-60.
4. The method for enriching and detecting microplastics in surface water according to claim 1, characterized in that: The carbon quantum dot active site microporous adsorbent is prepared by: S101, selecting calcium-based montmorillonite, adding the calcium-based montmorillonite to deionized water, adding dilute hydrochloric acid and stirring evenly, so that the calcium-based montmorillonite is dispersed in the dilute hydrochloric acid solution, heating to 60° C., adding dimethyldiallyl ammonium chloride, stirring fully, reacting for 1 to 2 hours, and obtaining an aminated montmorillonite suspension, adjusting the pH value to 5.0 to 5.5, adding histidine, stirring fully, and reacting for 1 to 2 hours to obtain an aminated montmorillonite microsphere suspension with a negative charge on the outside and a high density of cations on the inside; wherein the mass ratio of dimethyldiallyl ammonium chloride to calcium-based montmorillonite is 1:20; the mass ratio of the histidine to calcium-based montmorillonite is 1:4 to 5; S102, dissolving the carbon quantum dot active site powder in a citric acid aqueous solution with a mass concentration of 8% to activate the active sites on the carbon quantum dot active site powder, and then adding the suspension of aminated montmorillonite microspheres with negative charge on the outside and high density of cations on the inside obtained in S101, reacting at 50-60°C for 2-3 hours to allow the carbon quantum dot active site powder and montmorillonite microspheres to fully react and cross-link, filtering, and low-temperature drying to obtain a carbon quantum dot active site microporous adsorbent; the mass ratio of the carbon quantum dot active site powder to the calcium-based montmorillonite is 1:
5.
5. The method for enriching and detecting microplastics in surface water according to claim 1, characterized in that: The microplastics include but are not limited to at least one of polystyrene, polyethylene, polypropylene, polyvinyl chloride, polyethylene terephthalate, and polymethyl methacrylate.
6. The method for enriching and detecting microplastics in surface water according to claim 1, characterized in that: The adsorption treatment time is 40 to 50 minutes; the microporous membrane is a glass fiber membrane, and the pore size of the microporous membrane is 0.5 to 1 μm; the digestion solution is a mixed solution obtained by mixing tetrahydrofuran and dichloromethane in a mass ratio of 1:
3.
7. The method for enriching and detecting microplastics in surface water according to claim 1, characterized in that: The mass ratio of the adsorbent to the water sample of the surface water containing microplastics is 0.1 to 2:
100.
8. The method for enriching and detecting microplastics in surface water according to claim 1, characterized in that: This method based on liquid chromatography-mass spectrometry for quantitative detection of microplastics in water bodies is used in monitoring microplastic surface water environmental pollution.
Citation Information
Patent Citations
A method for quantitatively analyzing the enrichment and distribution of microplastics in aquatic organisms
CN105651748B
A method for determining the microplastic content in seawater and the absorption of microplastics by organisms.
CN107966393B
Methods for removing microplastics from water based on graphene materials
CN111569829B
Method for quantitatively analyzing enrichment and distribution of micro plastics in aquatic organisms
CN105651748A
Method for determining content of microplastics in seawater and organism-absorbed microplastics
CN107966393A
Cited By
Preparation method of extract and pig feed addition application
CN119563790A
Hydrophobic carbon dots as well as preparation method and application thereof
CN120059741A
Targeted enrichment-photocatalytic degradation method for one-stop removal of microplastics in water body
CN121292709A